Entreprenership in the conditions of modernization of national economy on innovative type (Путеводитель предпринимателя)
The paper considers modern stereotypes, issues of globalization and liberalization, is considered the level of innovation of the domestic economy and the necessity of an active economic policy. The assessment of global trends and some indicators of domestic development proved the special role of the business sector in the selected direction of modernization of the domestic economy to an innovative type.